Titanium carbonitride-based micro-nano composite ceramic tool material and preparation method thereof

By adding nano 3Y-ZrO2 and micron WC particles to the Ti(C0.7, N0.3)-based ceramic tool material, combined with a small amount of metal sintering agent, a titanium carbonitride-based micro-nano composite ceramic tool material with high fracture toughness and high hardness was prepared, which solved the problems of low fracture toughness and high metal bonding phase of the existing materials and improved the cutting processing performance.

CN117645485BActive Publication Date: 2025-04-04YANSHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311524698.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2025-04-04
Estimated Expiration
2043-11-15

AI Technical Summary

Technical Problem

The existing Ti(C0.7, N0.3)-based ceramic tool materials have low fracture toughness and bending strength, and the content of metal bonded phases is high, which limits its application when processing high hardness materials.

Method used

By adding nano-scale 3Y-ZrO2 particles and micro-scale WC particles to the titanium carbonitride matrix, combining a small amount of metal sintering agent, dispersing evenly using a silane coupling agent, and using a vacuum hot press sintering process to prepare titanium carbonitride-based micro-nano composite ceramic tool material.

Benefits of technology

The fracture toughness and bending strength of titanium carbonitride-based micro-nano composite ceramic tool materials are significantly improved, while reducing the content of metal bonded phases, maintaining high hardness, and improving cutting processing performance and tool life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117645485B_ABST
    Figure CN117645485B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material science and relates to a titanium carbonitride (Ti(C 0.7 ,N 0.3 ))-based micro-nano composite ceramic tool material and its preparation method. According to weight percentage, it includes the following raw materials: WC 10.0-30.0%, 3Y-ZrO 2 5.0~25.0%, sintering agent 3.0~5.0%, the balance is Ti(C 0.7 ,N 0.3 ); Among them, WC, sintering aid, Ti(C 0.7 ,N 0.3 ) particles are micrometer-sized, 3Y‑ZrO 2 The particles are nanometer-sized, and the sintering aids are Ni and Co; 3Y-ZrO 2 The titanium carbonitride-based micro-nano composite ceramic tool material provided by the present invention not only has high fracture toughness, but also greatly reduces the metal bonding phase, making it have high hardness, thus greatly improving the cutting performance and tool life of the titanium carbonitride-based micro-nano composite ceramic tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material science and relates to a titanium carbonitride (Ti(C 0.7 ,N 0.3 ))-based micro-nano composite ceramic tool material and its preparation method. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Compared with TiC and TiN based composite ceramic tool materials, Ti(C 0.7 ,N 0.3 )-based composite ceramic tool materials are widely used as tool materials due to their good mechanical properties, excellent thermal shock resistance, wear resistance and chemical stability. However, the limitation of Ti(C 0.7 ,N 0.3 )-based ceramics are used for their relatively low fracture toughness and high metal bonding phase. In addition, the melting point of the metal bonding phase is relatively low, and too much metal bonding phase is not suitable for processing materials with high cutting temperatures, such as titanium alloys, nickel-based alloys and other materials. Therefore, how to effectively improve the fracture toughness and bending strength of ceramic tool materials while reducing the metal bonding phase and promote its reliability in practical applications has become a major issue for Ti(C 0.7 ,N 0.3 ) is a key issue in the development of quartz-based ceramic tool materials.

[0004] In order to improve the mechanical properties of Ti(C0.7,N0.3) based composite ceramic materials, many scholars have conducted extensive research by optimizing the sintering process and adding secondary phases and nanophases. Among them, adding secondary phases and nanophases, such as carbides or nitrides, is an effective and easy-to-implement method to improve the mechanical properties of ceramic materials. Additive phases such as TaC, TiB2, Mo2C and WC not only play a vital role in improving the microstructure of Ti(C0.7,N0.3) based ceramic tool materials and inhibiting grain growth, but also improve the wettability between the ceramic phase and the bonding phase, and improve the mechanical properties of Ti(C 0.7 ,N 0.3 ) based ceramic tool materials.

[0005] In addition, due to the Ti(C 0.7 ,N 0.3 A large amount of metal binder phase needs to be added to Ti(C)-based ceramic tool materials. 0.7 ,N 0.3)-based ceramic material system adds 15 to 40 wt.% of metal binder phase, resulting in a hardness of only 13 to 15 GPa, which is insufficient for processing high hardness materials.

[0006] At present, scholars at home and abroad have studied the use of a variety of toughening mechanisms to improve the fracture toughness of ceramic tools, but the effect is not very ideal. For example, the toughening range of particle dispersion toughening is very limited; the toughening effect of ceramic tools decreases with the increase of cutting temperature, and the hardness decreases while the fracture toughness increases; whisker toughening can significantly improve the fracture toughness of ceramic tool materials, but it is expensive and the cost of use is too high. Summary of the invention

[0007] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a titanium carbonitride-based micro-nano composite ceramic tool material and a preparation method thereof. The titanium carbonitride-based micro-nano composite ceramic tool material provided by the present invention not only has high fracture toughness, but also greatly reduces the metal bonding phase, making it have high hardness, thereby greatly improving the cutting performance and tool life of the titanium carbonitride-based micro-nano composite ceramic tool.

[0008] In order to achieve the above object, the technical solution of the present invention is:

[0009] On the one hand, a titanium carbonitride-based micro-nano composite ceramic tool material comprises the following raw materials, measured by weight percentage: WC 10.0-30.0%, 3Y-ZrO2 5.0-25.0%, sintering aid 3.0-5.0%, and the balance Ti(C 0.7 ,N 0.3 ); Among them, WC, sintering aid, Ti(C 0.7 ,N 0.3 ) particles are micron-sized, 3Y-ZrO2 particles are nanometer-sized, and the sintering aids are Ni and Co; 3Y-ZrO2 is evenly dispersed by a silane coupling agent.

[0010] In the understanding of the traditional preparation method of metal ceramics, it is impossible to prepare high-strength titanium carbonitride-based ceramic tool materials by adding only 3.0-5.0% of metal sintering aids. The main difficulty lies in the abnormal growth of grains, low fracture toughness and flexural strength.

[0011] In order to improve the fracture toughness and flexural strength of titanium carbonitride-based ceramic tool materials, the present invention adds nano-scale 3Y-ZrO2 particles to the titanium carbonitride matrix. This is because 3Y-ZrO2 has high flexural strength and fracture toughness, and during the fracture process, when the tensile stress around the crack tip reaches a critical value, tm changes, which helps to improve toughness and form microcracks. Along with the transformation, the resulting shear deformation (1-7%) and volume expansion (4-5%) are introduced. The deformation effectively reduces the stress intensity and consumes the fracture energy. The volume expansion leads to the generation of compressive stress, which acts as a crack closure stress and improves the fracture toughness of the matrix. The fracture energy can be increased by an order of magnitude through phase transformation toughening. The nanoscale is used to exert its synergistic effect on the phase transformation toughening and fine grain strengthening of the material.

[0012] In order to prevent the hardness of the titanium carbonitride-based ceramic tool material with the addition of 3Y-ZrO2 from being greatly reduced, the present invention adds micron-sized WC particles to the titanium carbonitride matrix. The WC hard particles have a very high Vickers hardness. The presence of the WC particles can limit the grain boundary movement during the sintering process through the pinning effect on the grain boundary, and can inhibit the abnormal growth of grains, giving full play to the dispersion strengthening effect of the micron WC particles.

[0013] The present invention achieves synergistic toughening and strengthening effects by adding micron and nano particles simultaneously, thereby improving the bending strength and fracture toughness of titanium carbonitride-based ceramic tool materials, and maintaining a relatively high Vickers hardness by reducing the metal phase content.

[0014] Experiments have shown that the present invention can not only greatly reduce the metal bonding phase and significantly improve the hardness of titanium carbonitride-based ceramic tool materials, but also improve the bending strength and fracture toughness of titanium carbonitride-based ceramic tool materials to a certain extent.

[0015] On the other hand, a method for preparing the titanium carbonitride-based micro-nano composite ceramic tool material comprises using a silane coupling agent to uniformly disperse 3Y-ZrO2 in a dispersion medium to obtain a 3Y-ZrO2 dispersion, and then 0.7 ,N 0.3 ), WC and a sintering aid are added to the 3Y-ZrO2 dispersion and mixed evenly to obtain a composite ceramic slurry, and then the composite ceramic slurry is dried and sieved to obtain a composite ceramic powder; after the composite ceramic powder is pressed into shape, vacuum hot pressing is carried out under the conditions of a sintering pressure of 30 to 35 MPa, a heating rate of 5 to 15°C / min, and a sintering temperature of 1400 to 1600°C to obtain the composite ceramic slurry.

[0016] In a third aspect, the above-mentioned titanium carbonitride-based micro-nano composite ceramic tool material is used for cutting titanium alloys and the like.

[0017] The beneficial effects of the present invention are:

[0018] (1) The present invention gives full play to the synergistic toughening and strengthening effects of micro-nano and phase transformation to prepare titanium carbonitride-based composite ceramic tool materials with high comprehensive mechanical properties.

[0019] (2) Compared with the prior art, the nanoparticles of the composite ceramic tool material prepared by the method of the present invention are evenly dispersed, and the material density and comprehensive mechanical properties have obvious advantages.

[0020] (3) The titanium carbonitride-based micro-nano composite ceramic tool material prepared by the present invention using a small amount of metal sintering aid meets the "double high" requirements (high hardness and high fracture toughness), which can effectively improve the tool cutting performance and tool life. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1 This is a process flow chart of a method for preparing a titanium carbonitride-based micro-nano composite ceramic tool material according to Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of the fracture microstructure of the titanium carbonitride-based micro-nano composite ceramic tool material prepared in Example 1 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of the crack propagation path on the broken polishing surface of the titanium carbonitride-based micro-nano composite ceramic tool material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0026] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0027] In view of the fact that the existing titanium carbonitride-based micro-nano composite ceramic tool materials are difficult to simultaneously meet the requirements of high hardness, high fracture toughness and high bending strength, resulting in poor cutting performance and low tool life, the present invention proposes a titanium carbonitride-based micro-nano composite ceramic tool material and a preparation method thereof.

[0028] A typical embodiment of the present invention provides a titanium carbonitride-based micro-nano composite ceramic tool material, which comprises the following raw materials by weight percentage: WC 10.0-30.0%, 3Y-ZrO2 5.0-25.0%, sintering aid 3.0-5.0%, and the balance Ti(C 0.7 ,N 0.3 ); Among them, WC, sintering aid, Ti(C 0.7 ,N 0.3 ) particles are micron-sized, 3Y-ZrO2 particles are nanometer-sized, and the sintering aids are Ni and Co; ZrO2 is evenly dispersed by a silane coupling agent.

[0029] In some embodiments, WC 10.0-20.0%, 3Y-ZrO2 5.0-15.0%, sintering aid 3.0-5.0%, and the balance Ti(C 0.7 ,N 0.3 ).

[0030] In some embodiments, WC 13.0-17.0%, 3Y-ZrO2 8.0-12.0%, sintering aid 3.0-5.0%, and the balance Ti(C 0.7 ,N 0.3 ).

[0031] According to the Hall-Petch theory, the smaller the particle size, the higher the strength, but the hardness may decrease. Since WC is a hard phase, in some embodiments, the particle size of WC is 0.2-0.5 μm, ensuring high strength while taking into account a high Vickers hardness.

[0032] In some embodiments, the particle size of the sintering aid is 1-2 μm.

[0033] In some embodiments, the ceramic material matrix Ti (C 0.7 ,N 0.3 ) has a particle size of 0.5 to 1 μm.

[0034] Since the main function of 3Y-ZrO2 is toughening and strengthening, in some embodiments, the particle size of 3Y-ZrO2 is 40-60 nm, which can effectively exert the synergistic effect of phase transformation toughening and fine grain strengthening.

[0035] In some embodiments, the amount of the silane coupling agent added is 0.5-1.5% by weight of 3Y-ZrO2.

[0036] Another embodiment of the present invention provides a method for preparing the above-mentioned titanium carbonitride-based micro-nano composite ceramic tool material, using a silane coupling agent to evenly disperse 3Y-ZrO2 in a dispersion medium to obtain a 3Y-ZrO2 dispersion, and then Ti(C 0.7 ,N 0.3 ), WC and a sintering aid are added to the 3Y-ZrO2 dispersion and mixed evenly to obtain a composite ceramic slurry, and then the composite ceramic slurry is dried and sieved to obtain a composite ceramic powder; after the composite ceramic powder is pressed into shape, vacuum hot pressing is carried out under the conditions of a sintering pressure of 30 to 35 MPa, a heating rate of 5 to 15°C / min, and a temperature of 1400 to 1600°C to obtain the composite ceramic slurry.

[0037] The flexural strength of the sintered composite ceramic tool material is 800MPa-1400MPa, and the fracture toughness is 6.00MPa.m 1 / 2 -8.00MPa.m 1 / 2 , hardness is 16.00GPa-22.00GPa. Because the toughening and reinforcing effect of micron WC and nano ZrO2 particles in titanium carbonitride-based micro-nano composite ceramic tool materials improves the comprehensive mechanical properties of composite ceramic tool materials.

[0038] Since nanoparticles are prone to agglomeration, in some embodiments, 3Y-ZrO2 is first added to a dispersion medium to prepare a suspension, and then a silane coupling agent is added to perform stirring and / or ultrasonic dispersion to obtain a uniformly dispersed 3Y-ZrO2 dispersion.

[0039] In some embodiments, Ti(C 0.7 ,N 0.3 ), WC and sintering aids are added to the 3Y-ZrO2 dispersion for stirring and / or ultrasonic dispersion. Since the powder particle size is too small and there are differences and the powders are mixed unevenly, the sintering effect will be affected. Therefore, wet ball milling is required for mixing and crushing to obtain a uniformly dispersed composite ceramic slurry.

[0040] In some embodiments, the vacuum degree of vacuum hot pressing sintering is maintained for 10 -4 Pa or less. It is more conducive to ensuring the density of the material, thereby improving the mechanical properties of the material.

[0041] In some embodiments, the heat preservation and pressure holding time of vacuum hot pressing sintering is 30 to 75 minutes.

[0042] A third embodiment of the present invention provides a titanium carbonitride-based micro-nano composite ceramic tool material that can be used for cutting titanium alloys and the like.

[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0044] Example 1

[0045] Preparation method of titanium carbonitride-based micro-nano composite ceramic tool material, such as Figure 1 As shown, the steps are as follows:

[0046] (1)(1) With 0.5 μm titanium carbonitride (Ti(C 0.7 ,N 0.3 )), 0.25μm tungsten carbide (WC), 50nm zirconium oxide (3Y-ZrO2), 1μm cobalt (Co), 1μm nickel (Ni) as raw materials, according to 70.0Ti (C 0.7 ,N 0.3 )-15.0WC-10.0(3Y)-ZrO2-3.0Co-2.0Ni mass percentage mixture; weighed nano 3Y-ZrO2 powder in proportion with anhydrous ethanol as a dispersion medium, the nano 3Y-ZrO2 is prepared into a suspension, the concentration of the suspension is 2.0vol.%; then 1.0% of the mass of the nano 3Y-ZrO2 silane coupling agent is added to the suspension as a dispersant; then mechanical stirring and ultrasonic dispersion for 30min; then weighed micron Ti(C 0.7 ,N 0.3 ), WC and sintering aids are added to the uniformly dispersed 3Y-ZrO2 suspension and ultrasonically stirred for 30 minutes; then loaded into a ball mill and wet-milled with zirconia balls for 48 hours to obtain a uniformly dispersed composite ceramic slurry.

[0047] (2) The composite ceramic slurry obtained in step (1) is placed in a vacuum drying oven and dried at 120° C. for 6 h, then cooled to room temperature, sieved through a 200-mesh sieve, and the composite ceramic powder is obtained and packaged for later use.

[0048] (3) Calculate the powder weight of the composite ceramic powder obtained in step (2) according to the size of the mold and the thickness of the sintered ceramic sample, put the weighed composite ceramic powder into the mold, flatten it, and press it with a cold press for 30 minutes to form it.

[0049] (4) Place the green compact and mold obtained in step (3) into a hot pressing sintering furnace, and keep the vacuum degree of the hot pressing sintering furnace at 10 -4 Pa, under a sintering pressure of 32MPa, the temperature is raised to 1500℃ at a rate of 10℃ / min, the temperature is kept at this temperature and pressure for 45min, and then the furnace is cooled to room temperature to obtain titanium carbonitride-based micro-nano composite ceramic tool material.

[0050] Example 2

[0051] Preparation method of titanium carbonitride-based micro-nano composite ceramic tool material, such as Figure 1 As shown, the steps are as follows:

[0052] (1) 0.5 μm titanium carbonitride (Ti(C 0.7 ,N 0.3 )), 0.25μm tungsten carbide (WC), 50nm zirconium oxide (3Y-ZrO2), 1μm cobalt (Co), 1μm nickel (Ni) as raw materials, according to 65.0Ti (C 0.7 ,N 0.3 )-15.0WC-15.0(3Y)-ZrO2-3.0Co-2.0Ni mass percentage mixture; weighed nano 3Y-ZrO2 powder in proportion with anhydrous ethanol as a dispersion medium, the nano 3Y-ZrO2 is prepared into a suspension, the concentration of the suspension is 2.0vol.%; then 1.0% of the mass of the nano 3Y-ZrO2 silane coupling agent is added to the suspension as a dispersant; then mechanical stirring and ultrasonic dispersion for 30min; then weighed micron Ti(C 0.7 ,N 0.3 ), WC and sintering aids are added to the uniformly dispersed 3Y-ZrO2 suspension and ultrasonically stirred for 30 minutes; then loaded into a ball mill and wet-milled with zirconia balls for 48 hours to obtain a uniformly dispersed composite ceramic slurry.

[0053] (2) The composite ceramic slurry obtained in step (1) is placed in a vacuum drying oven and dried at 120° C. for 6 h, then cooled to room temperature, sieved through a 200-mesh sieve, and the composite ceramic powder is obtained and packaged for later use.

[0054] (3) Calculate the powder weight of the composite ceramic powder obtained in step (2) according to the size of the mold and the thickness of the sintered ceramic sample, put the weighed composite ceramic powder into the mold, flatten it, and press it with a cold press for 30 minutes to form it.

[0055] (4) Place the green compact and mold obtained in step (3) into a hot pressing sintering furnace, and keep the vacuum degree of the hot pressing sintering furnace at 10 -4 Pa, under a sintering pressure of 32MPa, the temperature is raised to 1500℃ at a rate of 10℃ / min, the temperature is kept at this temperature and pressure for 45min, and then the furnace is cooled to room temperature to obtain titanium carbonitride-based micro-nano composite ceramic tool material.

[0056] Example 3

[0057] Preparation method of titanium carbonitride-based micro-nano composite ceramic tool material, such as Figure 1 As shown, the steps are as follows:

[0058] (1) 0.5 μm titanium carbonitride (Ti(C 0.7 ,N 0.3)), 0.25μm tungsten carbide (WC), 50nm zirconium oxide (3Y-ZrO2), 1μm cobalt (Co), 1μm nickel (Ni) as raw materials, according to 60.0Ti (C 0.7 ,N 0.3 )-15.0WC-20.0(3Y)-ZrO2-3.0Co-2.0Ni mass percentage mixture; weighed nano 3Y-ZrO2 powder in proportion with anhydrous ethanol as a dispersion medium, the nano 3Y-ZrO2 is prepared into a suspension, the concentration of the suspension is 2.0vol.%; then 1.0% of the mass of the nano 3Y-ZrO2 silane coupling agent is added to the suspension as a dispersant; then mechanical stirring and ultrasonic dispersion for 30min; then weighed micron Ti(C 0.7 ,N 0.3 ), WC and sintering aids are added to the uniformly dispersed 3Y-ZrO2 suspension and ultrasonically stirred for 30 minutes; then loaded into a ball mill and wet-milled with zirconia balls for 48 hours to obtain a uniformly dispersed composite ceramic slurry.

[0059] (2) The composite ceramic slurry obtained in step (1) is placed in a vacuum drying oven and dried at 120° C. for 6 h, then cooled to room temperature, sieved through a 200-mesh sieve, and the composite ceramic powder is obtained and packaged for later use.

[0060] (3) Calculate the powder weight of the composite ceramic powder obtained in step (2) according to the size of the mold and the thickness of the sintered ceramic sample, put the weighed composite ceramic powder into the mold, flatten it, and press it with a cold press for 30 minutes to form it.

[0061] (4) Place the green compact and mold obtained in step (3) into a hot pressing sintering furnace, and keep the vacuum degree of the hot pressing sintering furnace at 10 -4 Pa, under a sintering pressure of 32MPa, the temperature is raised to 1500℃ at a rate of 10℃ / min, the temperature is kept at this temperature and pressure for 45min, and then the furnace is cooled to room temperature to obtain titanium carbonitride-based micro-nano composite ceramic tool material.

[0062] Three groups of experiments were repeated for each embodiment, and then the mechanical properties were tested. The flexural strength test used the three-point bending method with reference to the standard GB / T 6569-2006, the fracture toughness test used the reference indentation method, and the Vickers hardness test used the indentation method with reference to the standard GB / T 16534-2009. At least 3 valid data were obtained for each group of experiments, and the average value was finally taken. The results are shown in Table 1.

[0063] Table 1 Mechanical properties of titanium carbonitride-based micro-nano composite ceramic tool materials prepared in Example 1

[0064]

[0065] Table 1 shows that the titanium carbonitride-based ceramic tool material prepared by the present invention has excellent mechanical properties, especially has a Vickers hardness superior to that of traditional metal ceramics, proving that a high-strength and tough titanium carbonitride-based ceramic tool material can also be prepared with a low metal binder phase.

[0066] Figure 2 It shows that the grain distribution is relatively uniform and the number of pores is small, indicating that the density of the ceramic material is high, which is the premise for ensuring the excellent mechanical properties of the ceramic tool material. It can be seen that there are a large number of dissociation step surfaces on the fracture surface. Therefore, the fracture process is a mixed mode of transgranular fracture and intergranular fracture, and transgranular fracture is the main mode. This is conducive to the improvement of the mechanical properties of titanium carbonitride-based ceramic tool materials.

[0067] Figure 3 It shows that the crack propagation path is relatively tortuous, and crack bridging, crack bifurcation, crack deflection and transgranular fracture mechanisms occur during the propagation process, which makes the crack propagation consume more fracture energy, which is beneficial to improving the mechanical properties of titanium carbonitride-based ceramic tool materials.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A titanium carbonitride-based micro-nano composite ceramic tool material, characterized in that: According to weight percentage, it is composed of the following raw materials: WC 15.0%, 3Y-ZrO2 10.0%, sintering aid 5.0%, and the balance is Ti(C 0.7 ,N 0.3 ); Among them, WC, sintering aid, Ti(C 0.7 ,N 0.3 ) particles are micron-sized, 3Y-ZrO2 particles are nanometer-sized, and sintering aids are Ni and Co; 3Y-ZrO2 is evenly dispersed by a silane coupling agent; The particle size of WC is 0.2~0.5μm; The particle size of the sintering aid is 1~2μm; Ti(C 0.7 ,N 0.3 ) has a particle size of 0.5~1μm; The particle size of 3Y-ZrO2 is 40~60 nm; The amount of silane coupling agent added is 0.5~1.5% of the weight of 3Y-ZrO2.

2. A method for preparing the titanium carbonitride-based micro-nano composite ceramic tool material according to claim 1, characterized in that: Silane coupling agent is used to disperse 3Y-ZrO2 in the dispersion medium to obtain 3Y-ZrO2 dispersion, and then Ti(C 0.7 ,N 0.3 ), WC and a sintering aid are added to the 3Y-ZrO2 dispersion and mixed evenly to obtain a composite ceramic slurry, and then the composite ceramic slurry is dried and sieved to obtain a composite ceramic powder; after the composite ceramic powder is pressed into shape, vacuum hot pressing is carried out under the conditions of a sintering pressure of 30-35 MPa, a heating rate of 5-15°C / min, and a temperature of 1400-1600°C to obtain the composite ceramic slurry.

3. The method for preparing the titanium carbonitride-based micro-nano composite ceramic tool material according to claim 2, characterized in that: 3Y-ZrO2 is added to a dispersion medium to prepare a suspension, and then a silane coupling agent is added to perform stirring and / or ultrasonic dispersion to obtain a 3Y-ZrO2 dispersion.

4. The method for preparing the titanium carbonitride-based micro-nano composite ceramic tool material according to claim 2, characterized in that: Ti(C 0.7 ,N 0.3 ), WC and a sintering aid are added to a 3Y-ZrO2 dispersion for stirring and / or ultrasonic dispersion, and then wet ball milling is performed to obtain a composite ceramic slurry.

5. The method for preparing the titanium carbonitride-based micro-nano composite ceramic tool material according to claim 2, characterized in that: The vacuum degree of vacuum hot pressing sintering is maintained at 10 -4 Below Pa; Alternatively, the heat preservation and pressure holding time of vacuum hot pressing sintering is 30~75 min.

6. The titanium carbonitride-based micro-nano composite ceramic tool material according to claim 1 is used for cutting titanium alloy.

Citation Information

Patent Citations

  • Nano zirconia and micron tungsten carbide toughened and enhanced metal ceramic die material and preparation method thereof

    CN101956117A

  • Ti (C7, N3) / TiB2 / WC micro-nano composite metal ceramic cutter material and preparation method thereof

    CN115386759A